A capillary manometer for pressure measurements in small cavities. (April 2017) - Verbovšek, Tim; Šetina Batič, Barbara; Šetina, Janez; Kokalj, Tadej
Abstract: Measuring pressures inside small cavities is a demanding task, but an essential one for applications in microfluidics. Although several MEMS-based pressure sensors have already been demonstrated, their fabrication is complicated and they usually require external electronics, making their use onerous. In this paper we propose a simple, home-built, pressure sensor, based on a thin glass capillary. It is in its essence a gas manometer, where the position of a liquid plug inside a capillary, sealed at one end, is correlated with the pressure at the open end. By calibrating in a vacuum chamber, we achieved a pressure uncertainty of less than 10 mbar. The suitability of the sensor for characterizing polydimethylsiloxane (PDMS) pumps was tested by measuring air diffusion through PDMS rings. Permeability and diffusivity were determined from comparison to the numerical model, based on the finite-difference method (FDM). Their values at 25 °C were found to be 2.5 × 10 −6  cm 2 /s and 1.4 × 10 −5  cm 2 /s, respectively. Although the lifetime of this type of capillary manometer is limited by the evaporation of the liquid plug at low pressures, its small probe size and simple preparation make it a convenient and relatively accurate sensor to quickly measure the pressure in small cavities. Highlights: A simple capillary manometer for small cavity pressure measurements was constructed. Manometer can be easily manufactured and is independent of external electrical power. Traceability of pressure measurement is established only through length measurement. Its operation was verified on PDMS permeability measurement.